3DUI-EF: Towards a Framework for Easy Empirical Evaluation of 3D User Interfaces and Interaction Techniques - Domingues, Christophe; Otmane, Samir; Mallem, Malik (International Journal of Virtual Reality, 2010)
Designing usable and effective 3D User Interfaces and 3D Interaction Techniques is very challenging for Virtual Reality system developers and human factors specialists. Indeed, time consuming empirical evaluation is necessary to have an idea about the goodness of the 3D User Interface (3DUI) and the 3D Interaction Technique (3DIT) at the end of their development lifecycle. This may induce a huge loss of time if the result appears not to be satisfying in the end. Moreover, 3DUI evaluation is much more complex than 2D User Interfaces evaluation which is due to heterogeneous Virtual Reality (VR) devices and 3DIT. The aim of this work is to provide a framework allowing developers and experimenters to quickly evaluate 3DUIs and 3DITs during the design and the development lifecycle. The proposed framework is divided into two tools. The first one enables to create an evaluation protocol based on a knowledge database using two data mining algorithms, the "C4.5" to avoid from impossible combinations between devices and indicators and the "Spv Assoc Tree" to build a decision tree between indicators and factors. The second tool of the framework is an Evaluation Virtual Environment (EVE) to perform the evaluation according the protocol created with the first tool.